2022
DOI: 10.3390/su14095566
|View full text |Cite
|
Sign up to set email alerts
|

Could Social Bots’ Sentiment Engagement Shape Humans’ Sentiment on COVID-19 Vaccine Discussion on Twitter?

Abstract: During the COVID-19 pandemic, social media has become an emerging platform for the public to find information, share opinions, and seek coping strategies. Vaccination, one of the most effective public health interventions to control the COVID-19 pandemic, has become the focus of public online discussions. Several studies have demonstrated that social bots actively involved in topic discussions on social media and expressed their sentiments and emotions, which affected human users. However, it is unclear whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Studies also have shown that social media users prefer to exchange information with users in the same situation as themselves (Chan-Olmsted et al, 2013). Relying on the deep integration of artificial intelligence and social media, social bots have a stronger ability to hide and imitate, making it completely impossible for the public to recognize them with the naked eye (Zhang, Chen, et al, 2022). For the public, social bots that masquerade as regular users are their trusted social media friends.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also have shown that social media users prefer to exchange information with users in the same situation as themselves (Chan-Olmsted et al, 2013). Relying on the deep integration of artificial intelligence and social media, social bots have a stronger ability to hide and imitate, making it completely impossible for the public to recognize them with the naked eye (Zhang, Chen, et al, 2022). For the public, social bots that masquerade as regular users are their trusted social media friends.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some studies analyzed the role of bots regarding the spread of misinformation in general, while others have focused specifically on topics such as vaccines, conspiracy theories, hate speech, or reactions to other political actions [25][26][27][28][29][30][31]. However, a small amount of research compared the behavior of bots and humans [32,33].…”
Section: Unraveling the Use Of Disinformation Hashtags By Social Bots...mentioning
confidence: 99%
“…The BERT model also has an obvious advantage in sentiment analysis tasks [109]. Furthermore, optimized BERT and BERT-CNN models can even achieve about a 10% higher accuracy than LSTM (or Bi-LSTM) in sentiment analysis tasks [110][111][112]. However, BiLSTM models can achieve significantly higher results than the BERT model using a small dataset [113].…”
Section: Natural Language Processing and Text Miningmentioning
confidence: 99%